TELAAH FILOSOFIS ATAS ARSITEKTUR DIGITAL Kasus Studi Arsitektur Digital Neo-Nusantara di Ibu Kota Negara (IKN) - Rudyanto Soesilo (JoDA Journal of Digital Architecture, 2022)
All aspects of life cannot escape the development of the times with the last phenomenon being the influence of the development of the digital world which is called the process of "digitalization". Architecture as one aspect of life certainly does not escape undergoing this digitilization process. Aim this paper discusses the process of digitalizing architecture using a philosophical point of view. The research was conducted using Desk research, from data and existing literature. The data is then filtered according to its interrelationships, validity and adjusted to its needs. Then a predictive analysis was carried out to get a (hypothetical) conception of digital architecture digital architecture in IKN Nusantara. The results of this discussion are understanding of the application of the digital ontological paradigm into the architectural process carried out at IKN Nusantara as a study case and in the context of the creative economy, which is the future of the Indonesian Economy,  is very appropriate to develop a Neo-vernacular Digital Architecture in Indonesia which is hereinafter referred to as Neo-Nusantara Architecture.